The rise of stereotactic neurosurgery in Germany - Kinfe, Thomas M.; Coenen, Volker Arnd; Krauss, Joachim K. (Journal of neurological surgery. Part A, Central European neurosurgery, 2025)
The main purpose of this article is to report on the life, work, and achievements of functional neurosurgeons, neurologists, psychiatrists, and neuroanatomists located in Freiburg in the era of the newly founded Federal Republic of Germany along with the depiction of their long-lasting impact for functional stereotactic neurosurgery in Germany and abroad. Review of available literature (PubMed, Scopus, University Archiv of Freiburg, University Archiv Würzburg) and personal records (e.g., communications, biographical reports) was assessed and summarized providing an overview of the Freiburg School of Stereotaxy including the main protagonists Traugott Riechert (1905-1983), Rolf Hassler (1914-1984), Fritz Mundinger (1924-2012) along with Kurt Beringer (1893-1949), and Richard Jung (1911-1986) covering the years around 1950. The rise of stereotactic functional neurosurgery after World War II in Germany was inaugurated mainly by the Department of Neurosurgery in Freiburg through an interplay across neuro-associated disciplines. Close working relationships between the disciplines of neurosurgery (Traugott Riechert, Fritz Mundinger), neurology/psychiatry/neurophysiology (Kurt Beringer, Richard Jung), and neuroanatomy (Rolf Hassler) enabled the foundation, implementation, and further development of stereotactic techniques targeting movement disorders, psychiatric indications, pain, epilepsy, and brain tumors. Furthermore, educational efforts were undertaken to provide state-of-the-art stereotactic neurosurgery, which led to the spread of the so-called Freiburg School of Stereotaxy throughout Germany and beyond (Gert Dieckmann 1925-2007; Fritz Roeder 1906-1988/Hans Orthner 1914-2000; Konrad Nittner 1921-1994; Wilhelm Umbach 1915-1976, and others). The work and fate presented herein underlines the eminent role of the protagonists and the Freiburg School of Stereotaxy for the development and maintenance of functional stereotactic neurosurgery in Germany. This accounts for the broad range of treated neurological disorders along with the passion to steadily strive for innovations and education displayed by the dissemination of stereotactic functional neurosurgeons across German universities ultimately leading to an increased number of stand-alone functional units and/or departments over the coming decades of the past century.
Online veröffentlicht: 21. Mai 2025
Gesehen am 04.09.2025